Changes in livelihood pattern of inhabitants in waterlogged areas in south-west region in Bangladesh - Rejve, Kaiser (Department of Architecture, 2011)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2006.